Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6929534 10.53832/edtechhub.0123 2339240:7VEG4LSW 2405685:R4E96T5V 2405685:T9NZ63T3 2405685:VSHH2JUL
Keywords: _r:AddedByZotZen

Building an Acceptable Use Policy - Tanweer, Rabia; Wyss, Natalie (EdTech Hub, 2023)
Acceptable use policies (AUPs) aim to define how digital and technological tools and services (both devices and ICT services) should be used in or by education systems and actors. These policies address the rights, privileges, responsibilities, and ramifications associated with the use of technology in education spaces and for educational purposes. In doing so, AUPs attempt to promote good practice and responsible, safe use of the internet and digital technologies. This brief uses global examples of AUP policies and guidance on the development of AUPs to outline best practices and key considerations for the development of AUPs. Keywords: EdTech usage; acceptable use policy; tablets; laptops; desktop computers; EdTech hardware; EdTech software. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7754059 ZenodoArchiveConcept: 7754058 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521858 10.5281/zenodo.7754059 10.53832/edtechhub.0161 2405685:6E2WK46K
Keywords: _r:AddedByZotZen